Epidemiology and financial implications of self-inflicted burns. Issue 1 (February 2016) - George, S.; Javed, M.; Hemington-Gorse, S.; Wilson-Jones, N.
Highlights: We performed a retrospective review of the cost of managing self-inflicted burns. Major self-inflicted burns are one of the most costly conditions to treat. Major self-inflicted burns can be prevented. Abstract: Introduction: The cost of the treatment of burns is high especially in self-inflicted burns with prolonged treatment. We performed a retrospective review of the self-inflicted burns at our regional burns centre to determine the costs incurred in their management and to identify factors which could reduce the financial burden in the future. Methods: The data was collected retrospectively of all the inpatient and outpatient self-inflicted burns presenting to our regional burns centre in the year 2011. Results: Twenty one patients (out of a total of 870 patients) presented with self-inflicted burns to our centre in 2011. Five (23.8%) were major burns with an average of 53.2% Total Body Surface Area (TBSA) and 16 (76.2%) were minor burns with an average of 0.5% TBSA. 11 (52.4%) patients had flame burns including 4 self-immolation burns. The mortality rate was 4.8% ( n = 1). Five (23.8%) patients underwent surgical treatment. Seven (33.3%) patients were treated in intensive care and with average stay of 46.85 days. Critical care and theatre attendances made up most of the costs with average ICU stay per patient calculated at £313, 131/day. The total cost of all 21 patients was £1, 581, 856. Conclusion: Burns are preventable injuries, early detection and intervention in patients with propensity to self-inflict burns can possibly reduce the costs of treatment in the future.